2017
DOI: 10.1016/j.arthro.2017.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Secretome: A Potential Tool for the Prevention of Muscle Degenerative Changes Associated with Chronic Rotator Cuff Tears

Abstract: Mesenchymal stem cell secretome decreases the characteristic muscle degeneration associated with chronic rotator cuff tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 0 publications
2
45
1
Order By: Relevance
“…Oil Red O staining appeared to present less lipid accumulation in the cohorts having received ASC injections as shown in Figure . This is consistent with previous investigations suggesting that ASC secretome is capable of reducing lipid content in rotator cuff injuries . This finding however, is not consistent amongst the literature where injections of human vascular and adipose‐derived stem cells isolated from human stromal vascular fraction did not display significant changes in lipid reduction …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Oil Red O staining appeared to present less lipid accumulation in the cohorts having received ASC injections as shown in Figure . This is consistent with previous investigations suggesting that ASC secretome is capable of reducing lipid content in rotator cuff injuries . This finding however, is not consistent amongst the literature where injections of human vascular and adipose‐derived stem cells isolated from human stromal vascular fraction did not display significant changes in lipid reduction …”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with previous investigations suggesting that ASC secretome is capable of reducing lipid content in rotator cuff injuries. 33 This finding however, is not consistent amongst the literature where injections of human vascular and adipose-derived stem cells isolated from human stromal vascular fraction did not display significant changes in lipid reduction. 34 Upon denervation, the local cellular environment of skeletal muscle becomes altered, where presence of inflammatory cells amongst the muscle fibers increases.…”
Section: Discussioncontrasting
confidence: 62%
“…In the presence of local stem cell factories, a broader application of this concept may be envisioned as an off-the-shelf cell-free one-step therapy for tendon regeneration. The potential of this hypothesis has recently been suggested by Sevivas et al in preclinical models of rat rotator cuff tears [ 26 , 27 ]. These authors observed a decreased fatty degeneration and an increased muscular mass improved after local injection of human MSC secretome [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential of this hypothesis has recently been suggested by Sevivas et al in preclinical models of rat rotator cuff tears [ 26 , 27 ]. These authors observed a decreased fatty degeneration and an increased muscular mass improved after local injection of human MSC secretome [ 26 ]. The authors also noticed an anabolic effect of MSC secretome on human tendon cells in vitro and an improvement in enthesis reconstruction after implantation of the scaffolds seeded with human tendon cells pretreated with human MSC secretome [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, MRCTs are in fact very large tears that are difficult to repair and are often associated with an uncertain prognosis 15. Therefore, in order to assemble the greatest number of massive tears reported in different prospective studies, we included studies which reported the results of large-to-massive tears in the same group (minimum size of 3 cm) 30 31 33–36 38 39…”
Section: Discussionmentioning
confidence: 99%